PENGARUH INTERAKSI TEMAN SEBAYA TERHADAP HASIL BELAJAR SISWA - Vita Dian Nur Azizah; Lailla Hidayatul Amin; Alfian Eko Rochmawan (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
Lack of confidence interacting with peers makes it difficult for students to make friends with their peers, this also affects student learning outcomes. The purpose of this research is to find out how much influence peer interaction has on student learning outcomes at school. This research uses quantitative methods. The research subjects consisted of 54 students of class IV MIM Bentak. Data collection techniques were carried out by distributing questionnaires to students and documentation. The data analysis technique used is a descriptive technique. To test the validity of the data, validity and reliability tests were used. To test normality using help of the SPSS program. To test hypothesis using product moment correlation. The effect of peer interaction on student learning outcomes in class IV MIM Bentak was proven in the test calculation hypothesis with Product Moment correlation of 0,403. While the value of the table at the 5% significance level is 0,266. And the influence of peer interaction on student learning outcomes is obtained by a simple linear regression equation, Y= a + bX, Y = 167,798 + 0,072. In this study there was an influence of peer interaction on student learning outcomes of 0,403 > 0,266 so that in this study H0 was rejected and H1 was accepted. Peers can influence student learning outcomes, students who make friends easily and have positive values are able to change behavior and teach their peers in a positive direction and are able to improve learning outcomes.